2014
DOI: 10.1063/1.4894677
|View full text |Cite
|
Sign up to set email alerts
|

Glow discharge based device for solving mazes

Abstract: A glow discharge based device for solving mazes has been designed and tested. The device consists of a gas discharge chamber and maze-transformer of radial-azimuth type. It allows changing of the maze pattern in a short period of time (within several minutes). The device has been tested with low pressure air. Once switched on, a glow discharge has been shown to find the shortest way through the maze from the very first attempt, even if there is a section with potential barrier for electrons on the way. It has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Due to the great impact of plasma as a component in modern image viewing devices, the investigation of plasma tubes is of considerable interest. Additional applications of interest involve microfluidic chips proposed for visible analog computing 10 and the ability of glow discharges to find the shortest way through a maze 11 .…”
mentioning
confidence: 99%
“…Due to the great impact of plasma as a component in modern image viewing devices, the investigation of plasma tubes is of considerable interest. Additional applications of interest involve microfluidic chips proposed for visible analog computing 10 and the ability of glow discharges to find the shortest way through a maze 11 .…”
mentioning
confidence: 99%
“…It is amazing that even with such a tricky geometry of the labyrinth, plasma is capable to find the optimal way out! Moreover, the shortest path includes sections that require electrons to move away from the anode, the voltage needed to initiate a discharge drops …”
Section: Resultsmentioning
confidence: 99%
“…It is thus not surprising that the geometric and topological complexity of a maze and its solutions (i.e., one or more paths leading from the entrance to the exit) serves as a model configuration in many areas of science and technology (e.g., logistics, robot control, neuroscience, etc.). It has been shown that besides humans, animals, and computer algorithms, some amoeboid organisms [1][2][3], and even nonliving, synthetic constructs are 'able' to solve mazes [1][2][3][4][5][6][7][8][9][10][11][12]. Such chemical, physical or biological systems are initially in a non-equilibrium thermodynamic state with a spatial gradient of some thermodynamic variable, e.g., temperature, chemical potential, pressure, electric or magnetic field, which induces a flow of matter (momentum) or energy within the system to reach its equilibrium state.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic networks are often solved by imposing a pressure gradient across the corresponding maze [4] between the entrance and the exit so that the pressure-induced flow has the largest amplitude along the shortest path. An electric field gradient was used to induce a glow discharge in gas-filled microchannels and to identify the shortest path in mazes or urban city maps [5,6]; in a medium conducting electric current the shortest path is characterized by the largest gradient of the electric field which ionizes a gas and induces a plasma glow. Maze solving by a network of memristors is also based on the presence of an electric potential gradient [7].…”
Section: Introductionmentioning
confidence: 99%